Faktor yang Berhubungan dengan Status Gizi Anak Balita di Wilayah Kerja Puskesmas Atambua Selatan Kabupaten Belu - Anna Henny Talahatu; Jelin Adu; Afrona E. L Takaeb (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Nutritional problem in toddlers are still a public helath problem in the South Atambua sub-district, Belu district. The purpose of this study was to analyze factors related to children under five in the working area of the Atambua Selatan Helath Center, Belu Regency. The population in this study were all mothers with toddlers aged 12-59 montsh, totaling 2.126 toddlers. The sample consisted of 219 mothers with random sampling. Data analysis was performed by univariate analysis and bivariate analysis by Chi-Square test. This type of research is aquantitative study using a cross sectional design.  study uses a type of quantitative research with a cross-sectional study design with random sampling techiniques. Respondents in this study were mothers of toddlers, totaling 219 people. The study used univariate and bivariate analysis with the Chi Square test. The results of this study indicate that the variables related to nutritional status are knowledge (0,000), occupation (0,001), education (0,000) and food consumption (0,000). While the variable that is not related to nutritional status is income (0,721). Mother’s nutritional knowledge, mother’s occupation, mother’s education and food consumption have a significant relationship, while family income has no significant relationship with nutritional status. Community Healtg Centers are expected to be able to maximize counseling and counseling activities on a regular basis regarding toddler nutrition and the use of helath promotion media. As well as, the activie role of health workers is urgently needed, especially nutrition and health promotion staff to increase education efforts on the importance of nutritious food for toddlers.